Hubungan antara Social Anxiety dengan Loneliness pada Remaja yang Kecanduan Media Sosial TikTok di Kota Padang - Tiara Pabela; Rida Yanna Primanita (Lembaga Yasin AlSys, 2026)
Although social anxiety and loneliness have become a focus in various previous studies, research that specifically discusses the relationship between the two among adolescent TikTok users in local contexts, such as Padang City, remains limited. This study aims to analyze the relationship between social anxiety and loneliness among adolescent TikTok users. This study employed a quantitative approach with a correlational design, involving 100 adolescent participants aged 13–19 years who were selected through the purposive sampling technique. Data were collected using the UCLA Loneliness Scale and the Social Anxiety Scale for Adolescents (SAS-A), and were then analyzed using the Spearman correlation test because the data were not normally distributed. The results show a positive and significant relationship between social anxiety and loneliness among adolescent TikTok users (p = 0.003; r = 0.295). These findings contribute to the development of adolescent psychology studies, particularly regarding the relationship between social anxiety and loneliness in the context of social media use. The conclusion of the study emphasizes that the higher the social anxiety experienced by adolescents, the higher the tendency toward loneliness they feel in the context of TikTok use. The implications of this study include theoretical contributions to the adolescent psychology literature as well as practical implications for educational institutions and local government in Padang in designing psychosocial support efforts for adolescent social media users.